Examining the Impact of Cyberattacks on Women's Digital Security: Challenges and Solutions - Freshtah Fazel; Sonia Arsalan; Madina Ahmadi; Zainab Bahaduri; Tamanna Quraishi (Journal of Social and Humanities, 2025)
This study investigates the challenges faced by women in maintaining digital security amid rising cyberattacks and examines the effectiveness of gender-sensitive policies and educational programs aimed at improving women’s cybersecurity. As cyber threats increasingly target women, understanding their unique vulnerabilities and the role of specific protective measures is crucial. The research utilizes a quantitative approach with a structured questionnaire distributed to 150 participants across four faculties of an online university, including Medical, Economics, Education, and Computer Science. The data collected were analyzed to assess perceptions of digital security challenges, the effectiveness of gender-sensitive policies, and the importance of educational programs in enhancing women’s participation in cybersecurity. Results indicate that while gender-sensitive policies are viewed as somewhat effective, there is significant support for targeted educational programs to increase women’s involvement in cybersecurity. The findings highlight the need for more refined policies and better educational initiatives to address women’s unique digital security needs effectively. The study underscores the importance of implementing comprehensive strategies to improve women’s cybersecurity and promote their active participation in the sector.